Shunt Active Power Filter based on P-Q Theory with Multilevel Inverters for Harmonic Current Compensation - Suhendar Suhendar; Teguh Firmansyah; Alief Maulana; Zuldiag Zuldiag; Vektor Dewanto (Universitas Ahmad Dahlan, 2017)
A shunt active power filter based on P-Q theory combined with high pass filters (HPFs) for harmonic-current compensation was proposed in this paper. A dual level H-bridge inverter (DLHI) and clamp diode multilevel inverter (CDMI) as inverters was used. The proposed active power filter was applied to 3-phase power system with 220V voltage and 50Hz frequency. the simulation model was constructed by using Simulink MATLAB. The results show that the proposed active power filter with CDMI produces lower total harmonic distortion (THD) than the active power filters with DLHI. Additionally, the proposed shunt active power filter has lower THD compared with other types of active power filters.